Understanding the Paths of Surface Ozone Abatement in the Los Angeles Basin. Issue 4 (15th February 2022) - Kim, Si‐Wan; McDonald, Brian C.; Seo, Seunghwan; Kim, Kyoung‐Min; Trainer, Michael
Abstract: Ozone in the urban atmosphere can accumulate from photochemistry involving nitrogen oxides, carbon monoxide, and volatile organic compounds mainly emitted from fossil fuel combustions and volatile chemical products. Concentrated ozone near the earth's surface has a detrimental impact on the ecosystem and our health. The Los Angeles Basin is a classic example of an urban region with long‐standing ozone pollution, frequently in violation of its standard, designated by the US Environmental Protection Agency (EPA). Studies have reported substantial declines of ozone and their precursor concentrations over the past half century in this area due to extensive pollution controls. Since 2000, however, the ozone design value has remained the same and has not been able to fully reach the air quality standard set by the EPA despite decreases in its precursor concentrations. To understand this phenomenon, we utilize a chemical transport modeling approach to reproduce historical ozone trends and to conduct sensitivity runs relative to a 2010 baseline. Based on our analysis of the model simulations comparing the weekends and weekdays, rather than focusing only on the weekly averages, we diagnose that the Los Angeles Basin is actually going under a significant transition in photochemistry toward a lower ozone concentration. This reveals how air quality management strategies are slowly moving towards a pathway of reducing ozone concentrations in the future. Our study, however, suggests that further reductions of NOx emissions can lead to continued improvement of ozone pollution in this area. Key Points: Long‐term trends of ozone and its precursors concentrations in the LA Basin were simulated with the WRF‐Chem model Weekday and weekend ozone were almost identical or weekday ozone is higher than weekend ozone in the 2010s in the observation and model The model indicates that further reduction of NOx emissions decreases ozone in LA